Evaluating a capacity development intervention in health economics among producers and users of evidence in Nigeria: A case study in Getting Research Into Policy and Practice (GRIPP) in Anambra State - Charles C. Ezenduka; Obinna Emmanuel Onwujekwe (Health Economics Review, 2022)
Background: The use of research evidence to inform policy and practice cannot be overemphasized especially in low and middle-income countries (LMICs). To promote the use of research evidence in the provision of health services for enhanced effective control of communicable diseases in developing countries, the World Health Organization (WHO) in collaboration with the Health Policy Research Group (HPRG) commissioned a capacity development workshop in health economics among producers and users of research evidence in the healthcare system of Anambra state, south east Nigeria. This study was aimed to evaluate the impact of the workshop training on selected stakeholders on the use of health economics evidence to inform health policy and practice in the state. Methods: Participants were purposively selected based either as producers and users of evidence at various levels of healthcare decision making in Anambra state, comprising mostly senior managers and executives from the ministry of health, the academic and health institutions in the state. A two-day capacity development workshop was conducted to train the participants on the use of economic evidence to inform health policy and practice. Pre-post test approach and group exercises were used to assess the knowledge and impact of the training exercises on the participants regarding the use of health economics evidence. Analysis was based on the framework of process-output-outcome-impact approach using the pre-post test and scores technique to assess the impact of the training programme. Results: Pretest average scores varied from 39.7% to 60.5% while posttest scores varied from 47.6% to 65.7%, showing big differences in individual scores among participants, between the producers and users of evidence both prior to and after the training. The significant differences between the test scores indicated success in increasing the knowledge of participants on the use of health economics evidence. Results corroborated participants' perceptions that the workshop impacted positively on their ability to apply the knowledge of health economic evidence to inform decision making in their respective practices. Conclusion: Findings underscored the need for regular upgrade of stakeholders in the health system for enhanced uptake and sustainability of the programme to achieve the desired goal of getting research into policy and practice in the state applicable to other settings.
Keywords: 330; Capacity development; health economics; health policy and practice; research evidence; training workshop; healthcare system